Dark-Field Scanning Transmission Ion Microscopy via Detection of Forward-Scattered Helium Ions with a Microchannel Plate†. (6th May 2016) - Woehl, Taylor J.; White, Ryan M.; Keller, Robert R.
Abstract: A microchannel plate was used as an ion sensitive detector in a commercial helium ion microscope (HIM) for dark-field transmission imaging of nanomaterials, i.e. scanning transmission ion microscopy (STIM). In contrast to previous transmission HIM approaches that used secondary electron conversion holders, our new approach detects forward-scattered helium ions on a dedicated annular shaped ion sensitive detector. Minimum collection angles between 125 mrad and 325 mrad were obtained by varying the distance of the sample from the microchannel plate detector during imaging. Monte Carlo simulations were used to predict detector angular ranges at which dark-field images with atomic number contrast could be obtained. We demonstrate atomic number contrast imaging via scanning transmission ion imaging of silica-coated gold nanoparticles and magnetite nanoparticles. Although the resolution of STIM is known to be degraded by beam broadening in the substrate, we imaged magnetite nanoparticles with high contrast on a relatively thick silicon nitride substrate. We expect this new approach to annular dark-field STIM will open avenues for more quantitative ion imaging techniques and advance fundamental understanding of underlying ion scattering mechanisms leading to image formation.